2007
DOI: 10.2135/cropsci2006.05.0346
|View full text |Cite|
|
Sign up to set email alerts
|

Crop Rotation and Soil Amendment Alters Sorghum Grain Quality

Abstract: Soybean [Glycine max (L.) Merr.] rotation enhances grain sorghum [Sorghum bicolor (L.) Moench] yield, but influence on grain quality has not been measured. The objective was to determine the effect of cropping sequence (CS) and soil amendment (SA) on grain yield and quality. Sorghum grain yield and quality, soil NO3–N and water were measured in a rotation study in 2003 and 2004 on a Sharpsburg silty clay loam (fine, smectitic, mesic Typic Argiudoll). Cropping sequences were continuous sorghum, and sorghum rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Although the effects of rotation on soil mineral status are obvious, it was concluded that the explanation of rotation effects is beyond soil mineral status alone [20]. For example, it was found that crop rotation improved soil structure [14], soil organic matter [15], water use efficiency [16], enhanced mycorrhizal associations [21], improved grain quality [17] and crop nutrient use efficiency [16], decreased the variability in grain yield [18], improved weed control, and interrupt insect and disease cycles [16]. Maintaining optimum nutrient concentrations in soil resulted in higher seed protein and oleic fatty acid percentages [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of rotation on soil mineral status are obvious, it was concluded that the explanation of rotation effects is beyond soil mineral status alone [20]. For example, it was found that crop rotation improved soil structure [14], soil organic matter [15], water use efficiency [16], enhanced mycorrhizal associations [21], improved grain quality [17] and crop nutrient use efficiency [16], decreased the variability in grain yield [18], improved weed control, and interrupt insect and disease cycles [16]. Maintaining optimum nutrient concentrations in soil resulted in higher seed protein and oleic fatty acid percentages [5].…”
Section: Introductionmentioning
confidence: 99%
“…C rop rotation is a proven method of growing field crops. It is practiced worldwide for many purposes, including management or control of crop pests, improving soil physical and chemical properties, and ultimately increasing yield (Mady Kaye et al, 2007). A review of past research focused on temperate dryland wheat ( Triticum aestivum L.) production rotated with selected crops in northern Europe, southern Australia, and North America showed an average yield response of 20% or more (Kirkegaard et al, 2008).…”
mentioning
confidence: 99%
“…Furthermore, crop rotation could be used as an alternative approach to improve soil health and combat soil deterioration. It improves soil structure (Yazar, 2008), increases soil organic matter (Bremer et al, 2008;Bhatti and Khan, 2012) and water use efficiency (Tanaka et al, 2005), improves crop nutrient use efficiency (Karlen et al, 1994), reduces grain yield variability (Varvel, 2000) and improves grain quality (Kaye et al, 2007).…”
Section: Introductionmentioning
confidence: 99%